Registration of 'Judee' Wheat. Issue 2 (25th January 2013) - Carlson, G. R.; Berg, J. E.; Kephart, K. D.; Wichman, D. M.; Lamb, P. F.; Miller, J. H.; Stougaard, R. N.; Eckhoff, J. L.; Riveland, N. R.; Nash, D. L.; Grey, W. E.; Jin, Y.; et al.
Abstract : 'Judee' (Reg. No. CV‐1084, PI 665227) hard red winter (HRW) wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in September 2011. Judee has the pedigree 'Vanguard'/'Norstar'//'Judith' dwarf selection/3/'NuHorizon'. Judee was developed using a modified bulk‐breeding method and selected as an F5:6 headrow. Judee was tested under the experimental number MTS0713 from 2007 to 2011 in Montana. Quality was evaluated in multilocation Montana trials since 2007. Judee is a solid‐stem, high‐yielding HRW wheat line with medium to high test weight, medium maturity, reduced height ( Rht‐B1b ), medium to high grain protein, and acceptable milling and baking quality. Judee was released for its host‐plant resistance to wheat stem sawfly ( Cephus cinctus Nort.) conditioned by stem solidness, along with short stature and improved yield potential relative to existing solid‐stem cultivars adapted to Montana.